IMPACT OF ATMOSPHERIC AIR POLLUTION ON SANITARY CONDITIONS, WELL-BEING OF THE POPULATION AND ITS HYGIENIC ASSESSMENT (British Journal of Global Ecology and Sustainable Development, 2024)
Air pollution can be accompanied by a number of adverse consequences: damage to vegetation, reduced transparency of the atmosphere and visibility, an increase in the number of days with fogs, polluting the building and objects inside the apartments, destruction of materials as a result of chemical reactions. The adverse effect on humans of environmental pollution is recognized as determining almost all countries. This was also highlighted at the UN conference "Man and his external environment" held in Stockholm. It should be emphasized that the impact of environmental pollution on the human body extends much wider, which is a global problem of our planet. In the course of the development of the chemical industry, the relationship between a person and the environment, which affects all spheres of life, has become very complicated and continues to become more complicated, there has been a revolution not only in the branches of industrial production, but also in the conditions of our life, in connection with which many problems have arisen.